Collected writings of John Maynard Keynes Vol XVIII - Activities 1922-1932 End of reparations - Johnson, Elizabeth (Ed.); Keynes, John Maynard (Cambridge Cambridge University Press, 2013)
The decline of the mark 1921-1922